Use of Intersectionality Theory and Interpretive Descriptive Qualitative Method to Address Inequalities in Marginalized Communities - Kassam, Sadaf Murad (International Journal of Qualitative Research, 2024)
To understand the application of Intersectionality theory in conducting qualitative interpretative research on exploring inequalities and discriminatory healthcare practices towards marginalized communities. Method: Narrative Review. Data Sources: Systematic Literature search. Findings: Qualitative research on exploring discriminatory healthcare practices towards marginalized communities requires a research methodology that is practice-oriented and flexible in using theoretical knowledge. The theory of intersectionality exposes how socially constructed identities are intertwined with discriminatory healthcare practices toward marginalized communities. On the other hand, Interpretative Description (ID) is a clinical-based qualitative methodology that aims to identify gaps in healthcare and nursing practices and create evidence-based interventions to address such gaps. Using intersectionality with ID methodology allows researchers to identify discriminatory healthcare practices towards racialized communities and create resources to provide equalized care to marginalized communities. Conclusion: The theory of Intersectionality provides theoretical scaffolding to understand the impact of power, race, and social identities on marginalized populations. Using ID with intersectionality theory will be a novel approach to conducting research on marginalized communities and identifying ways to address the inequalities in nursing and healthcare practices.